2008
DOI: 10.1111/j.1095-8649.2007.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

A link between sound producing musculature and mating success in Atlantic cod

Abstract: Individual variability in the mating success of male Atlantic cod Gadus morhua was quantified within an aggregation (n ¼ 59) breeding undisturbed in a large (684 m 3 ) mesocosm tank. Observational and morphometric data were examined to assess the degree to which this mating variation could be explained by aspects of morphology, condition and spawning behaviour. The number of ventral mounts initiated (i.e. mating success) was highly variable; most mounts were initiated by a very small percentage of available ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 46 publications
0
12
1
Order By: Relevance
“…In other gadids, spawning activity and acoustic signalling seem to be tightly linked and primarily functions to attract females to spawning aggregations and provide a basis for mate selection (Burchard, Juanes, & Rountree, ; Hawkins & Rasmussen, ; Nordeide & Folstad, ; Nordeide & Kjellsby, ; Rowe & Hutchings, ; Rowe, Hutchings, Skjæraasen, & Bezanson, ). However, the specific function of acoustic signalling in burbot reproductive behaviour is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In other gadids, spawning activity and acoustic signalling seem to be tightly linked and primarily functions to attract females to spawning aggregations and provide a basis for mate selection (Burchard, Juanes, & Rountree, ; Hawkins & Rasmussen, ; Nordeide & Folstad, ; Nordeide & Kjellsby, ; Rowe & Hutchings, ; Rowe, Hutchings, Skjæraasen, & Bezanson, ). However, the specific function of acoustic signalling in burbot reproductive behaviour is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Both male and female cod produce grunts during the year; however, during the spawning season, only male cod grunt, both as part of an aggressive display to keep other males out of their territory and to attract females (Finstad & Nordeide 2004, Rowe & Hutchings 2006. Grunts are produced by the vibration of 3 pairs of muscles along the swimbladder wall (Brawn 1961b, Rowe & Hutchings 2008. The calls consist of short grunts (about 200 ms) with peak amplitudes at frequencies ranging between approximately 50 and 500 Hz (Brawn 1961b, Midling et al 2002, Finstad & Nordeide 2004.…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that G. morhua and P. pollachius produce more complex acoustic signals than has been reported, with modulations of both the characteristics of sounds and the rate of sound production that suggest a richer role of sound in mating and sexual reproduction in these fishes than has been previously appreciated. Sound production in G. morhua may be related to competition among males for access to females (Rowe & Hutchings, ) and directly linked to mating success (Rowe & Hutchings, ). It is common for male animals involved in competitive courtship to alter their behaviour in response to the actions of other males as such changes in behaviour can affect a male's ability to obtain mates.…”
Section: Discussionmentioning
confidence: 99%
“…Grunts, clicks, knocks, humming and rumbling sounds make up the acoustic repertoire of G. morhua (Brawn, 1961 a ; Midling et al , ; Vester et al , ; Rowe & Hutchings, , ; J. Nilsson, unpubl. data).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation